Orientia, rickettsia, and leptospira pathogens as causes of CNS infections in Laos: a prospective study - Sabine Dittrich, PhD; Sayaphet Rattanavong, MD; Sue J Lee, PhD; Phonepasith Panyanivong; Scott B Craig, PhD; Suhella M Tulsiani, PhD; Stuart D Blacksell, PhD; David A B Dance, FRCPath; Audrey Dubot-Pérès, PhD; Amphone Sengduangphachanh; Phonelavanh Phoumin; Daniel H Paris, MD; et al. (Elsevier, 2015)
Background: Scrub typhus (caused by Orientia tsutsugamushi), murine typhus (caused by Rickettsia typhi), and leptospirosis are common causes of febrile illness in Asia; meningitis and meningoencephalitis are severe complications. However, scarce data exist for the burden of these pathogens in patients with CNS disease in endemic countries. Laos is representative of vast economically poor rural areas in Asia with little medical information to guide public health policy. We assessed whether these pathogens are important causes of CNS infections in Laos. Methods: Between Jan 10, 2003, and Nov 25, 2011, we enrolled 1112 consecutive patients of all ages admitted with CNS symptoms or signs requiring a lumbar puncture at Mahosot Hospital, Vientiane, Laos. Microbiological examinations (culture, PCR, and serology) targeted so-called conventional bacterial infections (Streptococcus pneumoniae, Neisseria meningitidis, Haemophilus influenzae, S suis) and O tsutsugamushi, Rickettsia typhi/Rickettsia spp, and Leptospira spp infections in blood or cerebrospinal fluid (CSF). We analysed and compared causes and clinical and CSF characteristics between patient groups. Findings: 1051 (95%) of 1112 patients who presented had CSF available for analysis, of whom 254 (24%) had a CNS infection attributable to a bacterial or fungal pathogen. 90 (35%) of these 254 infections were caused by O tsutsugamushi, R typhi/Rickettsia spp, or Leptospira spp. These pathogens were significantly more frequent than conventional bacterial infections (90/1051 [9%] vs 42/1051 [4%]; p<0·0001) by use of conservative diagnostic definitions. CNS infections had a high mortality (236/876 [27%]), with 18% (13/71) for R typhi/Rickettsia spp, O tsutsugamushi, and Leptospira spp combined, and 33% (13/39) for conventional bacterial infections (p=0·076). Interpretation: Our data suggest that R typhi/Rickettsia spp, O tsutsugamushi, and Leptospira spp infections are important causes of CNS infections in Laos. Antibiotics, such as tetracyclines, needed for the treatment of murine typhus and scrub typhus, are not routinely advised for empirical treatment of CNS infections. These severely neglected infections represent a potentially large proportion of treatable CNS disease burden across vast endemic areas and need more attention. Funding: Wellcome Trust UK.